Identification of Potential RBPJ-Specific Inhibitors for Blocking Notch Signaling in Breast Cancer Using a Drug Repurposing Strategy - Mengjie Rui; Min Cai; Yu Zhou; Wen Zhang; Lianglai Gao; Ke Mi; Wei Ji; Dan Wang; Chunlai Feng (MDPI AG, 2022)
Notch signaling is a key parameter in regulating cell fate during tissue homeostasis, and an aberrant Notch pathway can result in mammary gland carcinoma and has been associated with poor breast cancer diagnosis. Although inhibiting Notch signaling would be advantageous in the treatment of breast cancer, the currently available Notch inhibitors have a variety of side effects and their clinical trials have been discontinued. Thus, in search of a more effective and safer Notch inhibitor, inhibiting recombinant signal binding protein for immunoglobin kappaJ region (RBPJ) specifically makes sense, as RBPJ forms a transcriptional complex that activates Notch signaling. From our established database of more than 10,527 compounds, a drug repurposing strategy-combined docking study and molecular dynamic simulation were used to identify novel RBPJ-specific inhibitors. The compounds with the best performance were examined using an in vitro cellular assay and an in vivo anticancer investigation. Finally, an FDA-approved antibiotic, fidaxomicin, was identified as a potential RBPJ inhibitor, and its ability to block RBPJ-dependent transcription and thereby inhibit breast cancer growth was experimentally verified. Our study demonstrated that fidaxomicin suppressed Notch signaling and may be repurposed for the treatment of breast cancer.